Generations of Transitional Justice in the World - Pathak, Bishnu (Advances in Social Sciences Research Journal, 2019)
The objectives of the paper are to investigate the axiomatic truth and record the human wrongdoings of the past, deliver justice to the victims at present, make perpetrators accountable and initiate generous change in the rule of law for prosperous, peaceful and harmonious nation. The state-of-the-art paper is prepared based upon literature review, exchanging and sharing, and a practical observation approach rather than theoretical-analytical conception, except Generation. An interdisciplinary (politico-legal) word, ‘Transitional Justice’ (TJ) is healing the violations and/or abuses of yesterday, investigating and reconciling today and hoping to protect the tomorrow for not only a few privileged, but for the people of all Generations. The Generation tends to ascertain cause, nature, degree and patterns of identity-based crimes and genocide, determine the role of perpetrators and analyze the impact of the Truth Commission. Generally, Generation refers to the biological age groupings (20 to 30 years) that live together and share similar characteristics – attitudes, behaviors, contexts, sufferings and cultures. The paper reviews over 90 TJ countries in Five Generations (I, II, III, IV and 0), starting from the post-World War II to the present day world. Generation-I presents a genesis of TJ, a notion changed from the holocaust to the retributive justice which comprises the analyses of Nuremberg Trial and Tokyo Tribunal. Rather than making the main perpetrators involved in World War (WW) II accountable, the Nuremberg Trial has been a holier-than-thou betrayal to the Germans by a pseudo trial, and immunity to ‘French, Soviet Union, Americans, British and Japanese Emperor’ and Geneva Convention violators owing to a high political masquerading and retribution. Generation-II reveals a notion changed from internecine war crimes to humanitarian justice. It compares and contrasts the functions of the Truth Commissions that have a direct structural link with perpetrators’ four Ds (viz. delay, deceive, deny and dilute) approaches of TJ. Beyond domestication, TJ is an international human rights law, international criminal law and international humanitarian law. TJ has been more political in nature and less legal in practice. Generation-III tends to a notion changed from domestic criminal jurisprudence to international tribunal justice. The western developed and non-signatory nations of the Rome Statute try hard to establish and control the International Criminal Court (ICC) to their bad relation with post-conflict countries. Generation-IV discloses a notion changed from sectarian violence to reconcile justice. In such cases, non-state elite actors normally engage against the weak and poor people to prove their superiority conducting communal apartheid and cultural genocide. Lastly, Generation-0 (Zero) refers to a notion changed for justice establishing the Truth Commission. Truth Commissions have been unable to identify and investigate the human rights violations and/or abuses in the post-conflict periods, despite huge national and international pressures. Generally, what for transitional justice: victor (perpetrator) or loser (victim and or survivor)? The answer is: ‘world’s Transitional Justice ironically ensures freedom to the perpetrators further limiting justice to the poor and weak victims and society at large’ in all Generations. On the other, the universe moves towards the identity-based multi-polar new world order setting owing to innumerable interests and practices of the Transitional Justice system.